Comparison of the ramp and step incremental exercise test protocols in assessing the maximal fat oxidation rate in youth cyclists - Michalik, K.; Danek, N.; Zaton, M. (Journal of Human Kinetics, 2021)
The incremental exercise test is the most common method in assessing the maximal fat oxidation (MFO) rate. The main aim of the study was to determine whether the progressive linear RAMP test can be used to assess the maximal fat oxidation rate along with the intensities that trigger its maximal (FATmax) and its minimal (FATmin) values. Our study comprised 57 young road cyclists who were tested in random order. Each of them was submitted to two incremental exercise tests on an electro-magnetically braked cycle-ergometer - STEP (50 W·3 min-1) and RAMP (~0.278 W/s) at a 7-day interval. A stoichiometric equation was used to calculate the fat oxidation rate, while the metabolic thresholds were defined by analyzing ventilation gases. The Student`s T-test, Bland-Altman plots and Pearson`s linear correlations were resorted to in the process of statistical analysis. No statistically significant MFO variances occurred between the tests (p = 0.12) and its rate amounted to 0.57 ± 0.15 g/min and 0.53 ± 0.17 g/min in the STEP and RAMP, respectively. No statistically significant variances in the absolute and relative (to maximal) values of oxygen uptake and heart rate were discerned at the FATmax and FATmin intensities. The RAMP test displayed very strong oxygen uptake correlations between the aerobic threshold and FATmax (r = 0.93, R2 = 0.87, p < 0.001) as well as the anaerobic threshold and FATmin (r = 0.88, R2 = 0.78, p < 0.001). Our results corroborate our hypothesis that the incremental RAMP test as well as the STEP test are reliable tools in assessing MFO, FATmax and FATmin intensities.